Non-enzymatic oxylipin production in a mudflat microphytobenthic biofilm: evidence of a diatom response to light - Doose, Caroline; Oger, Camille; Mas-Normand, Lindsay; Durand, Thierry; Hubas, Cédric (Frontiers in Photobiology, 2024)
Microphytobenthos (MPB) are a diatom-dominated microbial community of primary producers that inhabit mudflat sediments. The benthic diatoms display photo-protective strategies to face extreme light variations susceptible to generate cellular oxidative stress. However, oxidative stress induces the production of reactive oxygen species (ROS) that generate oxylipins—oxygenated metabolites of polyunsaturated fatty acids (PUFAs) —which are among the known chemical mediators in diatoms. Non-enzymatically generated oxylipins known as “isoprostanoids” or “isofuranoids” are poorly studied in diatoms. To better understand the roles of the latter in migrational MPB light response, we investigated the effect of different irradiances corresponding to dark (D), low light (LL, 50 and 100 μmol. photons. m−2. s−1PAR), medium light (ML, 250 μmol. photons. m−2. s−1 PAR), and high light (HL, 500, 750, and 1000 μmol. photons. m−2. s−1 PAR) on isoprostanoid production by the biofilm’s organisms. The PUFA precursors of the varying oxylipins evidenced a diatom response to irradiance. Under 1000 PAR, the total amount of isoprotanoids increased, indicating an oxidative stress response. Isoprostanes (IsoPs) and prostaglandins (PGs) characterized HL conditions and evidenced lipid peroxidation, probably linked to the higher generation of ROS by photosynthesis. In contrast, phytoprostanes (PhytoPs) characterized LL and ML, where the ROS scavengers were probably not overwhelmed. This first investigation of non-enzymatic oxylipin production by a microphytobenthic biofilm under different irradiances highlighted the potential of exploring their possible signaling roles related to MPB light responses.